İflas dışı adi konkordatoda konkordatonun tasdiki - Karakaya, Ahmet (İstanbul Medipol Üniversitesi, Sosyal Bilimler Enstitüsü, 2022)
Konkordato, borçlarını vadesinde ödeyemeyen veya ödeyememe tehlikesi altında bulunan borçluya, borçlarını ödeyebilmesi için fırsatlar tanıyan bir kurumdur. Borçlunun borçlarını konkordatonun imkanlarından faydalanarak ödeyebilmesi ise belli şartların gerçekleşmesine bağlıdır. Bu şartların bir kısmı İcra ve İflas Kanununun 305. maddesinde düzenlenirken, diğer bir kısmı ise konkordatonun özünden gelen şartlardır. Bu şartlardan öne çıkanı, konkordatonun Kanun'da öngörülen çoğunluk tarafından kabul edilmesidir. Alacakların Kanun'da öngörülen çoğunluğunun olumlu oyuna bağlı olan konkordatonun, azınlıkta kalan alacaklıların haklarının korunmasına yönelik şartları da mevcuttur. Azınlıkta kalan alacaklıların haklarını koruyan en önemli tasdik şartı ise, teklifle kaynakların orantılı olması şartıdır. Bu tasdik şartına göre borçlunun borçlarını, mali imkanları ölçüsünde, alacaklıların en üst seviyede tatmin olacakları şekilde ödemesi gerekmektedir.

Concordat is an instrument that provides opportunities to the debtor, who is not able to pay his/her debts on time or he/she is under the danger of being not to be able to pay them. Paying of the debtor his/her debts by benefiting from the opportunities of concordat depends on the realization of some certain conditions. As some of these conditions are regulated in the article no. 305 of Enforcement and Bankruptcy Law, others are the conditions that come from the essence of the concordat. The prominent one of these conditions, which is anticipated by the law, is the acceptance of the concordat by the majority. There are also conditions of concordat, that depends on the majority of the positive votes as anticipated in the law and aimed at protecting of the creditors, who are in minority. The most important approval condition that protects the creditors, who remain in minority, is being of the proposal proportionate to the resources. According to this approval condition, the debtor is required to pay his/her debts at the highest level that will satisfy the creditors in accordance with his/her financial capabilities.
Confirmation of concordat in non-bankruptcy ordinary concordat
Keywords: Konkordato; Konkordato Kaynakları; İflas; Concordat; Concordat Resources; Bankruptcy